PENGARUH PEMBINAAN PEMERINTAH, PHRI DAN STAKEHOLDER LAINNYA TERHADAP RETENSI KARYAWAN HOTEL MELALUI VARIABEL INTERVENING PELATIHAN - Sandi, M. Yusuf; Hardian, Dafyar Eliadi; Mulyadi, Edi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
High employee turnover is a strategic issue in the hospitality sector, particularly at MaxOne Hotel & Resort Makassar. This study aims to analyze the effect of guidance from the government, the Indonesian Hotel and Restaurant Association (PHRI), and other stakeholders on employee retention, with training as an intervening variable. A quantitative approach was used by distributing questionnaires to 118 respondents, then processed using SPSS software. The results show that the guidance from the government and PHRI has a direct, positive, and significant effect on employee retention. Stakeholder guidance does not have a direct significant effect, but it has a significant indirect effect through training. Simultaneously, all three forms of guidance positively contribute to retention. Training was found not to mediate the effect of government and PHRI guidance, but it fully mediates the effect of stakeholder guidance. This concludes that training is a crucial path in the effectiveness of external guidance. Thus, an integrated guidance strategy involving the active role of stakeholders needs to be developed to enhance employee loyalty and continuity of employment in the hotel sector. Keywords: Hospitality Industry, Human Resource Management, Employee Training, Stakeholder Coaching, Employee Retention